Wages and seniority when coworkers matter: estimating a joint production economy using Norwegian administrative data - Christopher Ferrall; Kjell G. Salvanes; Erik Ø. Sørensen (Institute for the Study of Labor (IZA), 2009)
We develop an equilibrium model of wages and estimate it using administrative data from Norway. Coworkers interact through a task-assignment model, and wages are determined through multilateral bargaining over the surplus that accrues to the workforce. Seniority affects wages through workplace output and relative bargaining power. These channels are separately identified by imposing equilibrium restrictions on data observing all workers within workplaces. We find joint production is important. Seniority affects bargaining power but is unproductive. We reinterpret gender and firm-size effects in wages in light of the rejection of linearly separable production.
urn:nbn:de:101:1-20090513287
Keywords: D2; J3; J24; L25; J7; 330; Wage distributions; productivity; matched data; multilateral bargaining; assignment models; Lohnniveau; Lohnverhandlungen; Betriebszugehörigkeit; Geschlecht; Produktivität; Norwegen